2011
DOI: 10.1074/jbc.m110.200881
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of the RNA-editing Enzyme ADAR2 for Normal Physiology in Mice

Abstract: ADAR2, an RNA editing enzyme that converts specific adenosines to inosines in certain pre-mRNAs, often leading to amino acid substitutions in the encoded proteins, is mainly expressed in brain. Of all ADAR2-mediated edits, a single one in the pre-mRNA of the AMPA receptor subunit GluA2 is essential for survival. Hence, early postnatal death of mice lacking ADAR2 is averted when the critical edit is engineered into both GluA2 encoding Gria2 alleles. Adar2 ؊/؊ /Gria2 R/R mice display normal appearance and life s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 42 publications
2
83
0
Order By: Relevance
“…Accordingly, known ADAR2 target sites, such as CYFIP2 (Nishimoto et al 2008;Riedmann et al 2008;Horsch et al 2011) or KCNA1 (Horsch et al 2011), showed no evidence of editing. Given the high expression level of ADAR, we expect A-to-G changes to occur frequently in our samples.…”
Section: Detection Of Editing Sites Genome Widementioning
confidence: 99%
“…Accordingly, known ADAR2 target sites, such as CYFIP2 (Nishimoto et al 2008;Riedmann et al 2008;Horsch et al 2011) or KCNA1 (Horsch et al 2011), showed no evidence of editing. Given the high expression level of ADAR, we expect A-to-G changes to occur frequently in our samples.…”
Section: Detection Of Editing Sites Genome Widementioning
confidence: 99%
“…Three ADAR gene family members (ADAR1-3) have been identified in mammals. ADAR (ADAR1) and ADARB1 (ADAR2) can be detected in many tissues, while ADARB2 (ADAR3) seems to be restricted to the brain (Jacobs et al 2009;Horsch et al 2011;Savva et al 2012). It is believed that ADAR and ADARB1 are the main catalytic enzymes that are accountable for all A-to-I editing activity, while the third member, ADARB2 (ADAR3), lacks a catalytic domain and its function is yet unclear .…”
Section: Introductionmentioning
confidence: 99%
“…A-to-I deamination is catalyzed by members of the adenosine deaminase (ADAR) family of enzymes that act on dsRNA and occurs mainly in the primate-specific Alu repetitive elements (Nishikura 2016). ADARs are extremely important for the maintenance of cell homeostasis as mouse null mutants develop epileptic seizures and die several weeks after birth (Higuchi et al 2000;Horsch et al 2011). In addition, dysregulated RNA editing levels at specific recoding sites have been linked with a variety of diseases including neurological or psychiatric disorders and cancer (Chen et al 2013;Behm and Öhman 2016;Khermesh et al 2016).…”
Section: Introductionmentioning
confidence: 99%